Meningkatkan kemampuan berinteraksi sosial melalui kegiatan pekan dolanan pada peserta didik kelompok B di Ra Al-Hidayah Pronojiwo Kabupaten Lumajang - Lestari, Fitri Dewi; Asmah, Ayu; Akbar, Mochamad Ramli (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2025)
This research is motivated by the importance of developing social interaction skills in early childhood in the formation of social intelligence in the future. However, many early childhood still experience difficulties in communicating, collaborating, and resolving conflicts positively. Therefore, to improve social interaction skills in group B students at RA Al-Hidayah Pronojiwo, researchers packaged traditional game activities in the form of Pekan Dolanan. The research method used was classroom action research (PTK) which was implemented in two cycles. Each cycle consisted of 4 stages. Pekan Dolanan activities were designed in a structured and fun way through various traditional games that emphasized aspects of collaboration and active involvement of children. The results of the research conducted at RA Al-Hidayah Pronojiwo showed that there was a significant increase in children's social interaction skills. Quantitative data recorded an increase from 37.5% in the pre-action to 81.3% in the second cycle. The conclusion of this study is that Pekan Dolanan is an effective and relevant pedagogical approach to improving social interaction skills in early childhood.